Narrative change in Gloria Films: Comparing various processes of therapeutic innovation - Barbosa, Eunice (2017)
Aims: The present study focuses on the analysis of novelty emergence in classic Gloria Films with Rogers, Perls, and Ellis to understand how the same client formulated her own problem and if and how change occurred in those three sessions. Method: The Innovative Moments Coding System was applied to track innovative moments (IMs) and their themes. Results: The session with Rogers showed more diversity in disclosed problems and themes of IMs, as well as a higher proportion of reflection IMs. The session with Perls demonstrated a high proportion of protest IMs. The session with Ellis showed less innovation than other sessions. The changes found were based mostly on reflection and protest IMs in three sessions. Conclusion: Narrative innovations occurred in the three single sessions. The type of dominant innovation is consistent with the therapeutic model and the IMs model. The exploration of the IMs’ themes allowed a more precise identification of Gloria's new narrative positions and their development throughout those sessions.